ESTIMATION OF RADIOMETRIC PERFORMANCE OF ELEKCTRO-OPTICAL IMAGING SENSOR OF LOW EARTH EQUATORIAL ORBIT LAPAN SATTELITE - Ahmad Maryanto; Andy Indradjad; Dinari Nikken Sirin; Ayom Widipaminto (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2012)
Study of spectro-radiometric performance of electro-optical imager which is planned to be launched on low earth equatorial orbit LAPAN satellite was conducted through simulative calculation of image irradiance and its associated generated voltage at the image detector output. Simulative calculation was applied to three scenarios of selected spectral bands. Those spectral bands were selected spectra (1), which consisted of spectral bands B = (390-540 and 790-900) nm, G = (470-610 and 700-900 ) nm, and R = (590-650 and 650-900) nm; selected spectra (2) consisted of B1 = (390-540) nm, G1 = (470-610) nm, and R1 = (590-650) nm; and selected spectra (3) consisted of B1(Green) = (525-605) nm, B2(Red) = (630-690) nm, and B3(NIR) = (750-900) nm, on three scenarios of optical aperture or f-number (N) 2.8, 4.0, and 5.6. Green grasses, dry grasses, and conifers were examples of the imaged target, chosen as representation of vegetations. Kodak KLI-8023 was used as the optical detector. The integration time was assumed 3 miliseconds which correspond to about 20 m ground sampling distance (GSD). Solar zenith angle were varying from 90 (early morning) to 0 (solar noon). The results showed that option (3) of selected spectra, as proposed for pushbroom imager of LAPAN satellite, was relatively accepted to be implemented and complemented with f-number 4.0 of optical system used. Whereas simulation RGB color displayed composed by R = B2(Red), G = B3(NIR), B = B1(Green) also showed a greenish color sense as expected for vegetation imaged target.